Challenges faced in implementing a functional environmental education programme in secondary schools: a case of Mhondoro-Mubaira Cluster, Chegutu District. - Matsa, Margaret Ruramai (Midlands State University, 2017)
The purpose of this study was to establish the challenges faced in implementing a functional environmental education programme in secondary schools. The researcher used a descriptive survey design because it gave a descriptive picture to the data obtained through observations, interviews and questionnaires. The sample consisted of twelve teachers and forty students from schools in Mhondoro-Mubaira Cluster. Questionnaires, interviews and observations were used as data generation tools. Research findings established that the teaching of environmental education was limited in schools due to lack of time, lack of qualified environmental educationists, lack of teaching and learning materials, lack of support, lack of funding and huge class sizes. The results suggest that a lot has to be done to improve environmental education in Mhondoro-Mubaira Cluster. Recommendations were suggested as intervention strategies aimed at eradicating the major challenges that were hindering the implementation of environmental education. Training, making environmental education a core subject, creation of clubs, provision of qualified teachers, sourcing teaching and learning materials from other ministries were some of the ways of improving environmental education in Mhondoro-Mubaira Cluster.